1993
DOI: 10.1093/infdis/168.5.1314
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Candida albicans Translocation from the Gastrointestinal Tract of Mice by Oral Administration of Saccharomyces boulardii

Abstract: Microbial translocation is defined as the passage of viable microbes from the gastrointestinal (GI) tract to extraintestinal sites, such as the mesenteric lymph node (MLN), spleen, liver, kidneys, and blood. The ability of orally administered viable Saccharomyces boulardii to inhibit Candida albicans translocation from the GI tract was tested in antibiotic-decontaminated, specific pathogen-free (SPF) mice, which were orally challenged with C. albicans to promote intestinal overgrowth and subsequent translocati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
6

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 11 publications
0
46
0
6
Order By: Relevance
“…Because of the long-standing use of Sb in infectious diarrhea, most experimental research from in vitro studies with organoid or cell cultures and animal models have focused on the prevention of microbial pathogen adherence (46,58), translocation of the commensal microbial flora (8,26), investigation of neutralization of bacterial toxins [i.e., Clostridium difficile toxin A (14,16,45) or Cholera toxin (9)], toxin-related signaling (9,18,19), maintenance of normal intestinal permeability and barrier function (45), as well as control of mucosal electrolyte transport and luminal secretion (16,27,28,45,50).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the long-standing use of Sb in infectious diarrhea, most experimental research from in vitro studies with organoid or cell cultures and animal models have focused on the prevention of microbial pathogen adherence (46,58), translocation of the commensal microbial flora (8,26), investigation of neutralization of bacterial toxins [i.e., Clostridium difficile toxin A (14,16,45) or Cholera toxin (9)], toxin-related signaling (9,18,19), maintenance of normal intestinal permeability and barrier function (45), as well as control of mucosal electrolyte transport and luminal secretion (16,27,28,45,50).…”
Section: Discussionmentioning
confidence: 99%
“…S. boulardii was isolated from fruit in Indochina, and because of its benefits in the treatment of diarrhea, it is now a commercially available alternative remedy in Europe, Africa, and South America (39,45) for AAD, acute diarrhea in children, and traveler's diarrhea (22). Many in vitro and some in vivo studies have suggested that S. boulardii is able to prevent intestinal infections caused by the adherence or invasion of C. difficile, Escherichia coli, and Candida albicans to the epithelial layer of the gastrointestinal tract (4,11,12). The efficacy of S. boulardii reported in case studies and in vitro trials (11) has led to investigations of the mechanisms involved in the probiotic activity of this yeast.…”
mentioning
confidence: 99%
“…O tratamento por via oral de camundongos gnotobióticos com Saccharomyces boulardii reduziu de 10 a 50 vezes a população intestinal de Candida albicans, provavelmente por algum tipo de imunoestimulação 27 . Em camundongos imunossuprimidos (descontaminação por antibióticos e injeções de prednisolona), a administração oral de Saccharomyces boulardii reduziu a freqüência de translocação de Candida albicans para os linfonodos mesentéricos, fígado e rins 28 . O tratamento com doses inferiores à posologia normal do Saccharomyces boulardii, em camundongos imunossuprimidos (ciclofosfamida), protegeu também os animais conforme revelam os dados de (i) translocação bacteriana para linfonodos mesentéricos, fígado e baço; (ii) histopatologia da mucosa intestinal e (iii) sobrevivência 29 .…”
Section: Proteção Ecológicaunclassified
“…Em camundongos, a administração do Saccharomyces boulardii por 70 dias na água de beber, na concentração de 5%, não levou a translocação do trato gastrintestinal para outros órgãos 76 . Em modelos de animais imunossuprimidos (prednisolona e descontaminação por antibiótico), o Saccharomyces boulardii foi encontrado em baixas concentrações nos linfonodos mesentéricos, não sendo detectados no fígado, baço ou rins 28 . Em estudos utilizando camundongos convencionais imunossuprimidos com ciclofosfamida e recebendo por via oral doses variadas de Saccharomyces boulardii (0,1mg; 1,0mg e 10mg ) por 7 dias, encontrou-se, independente da dose, translocação da levedura em baixas concentrações, principalmente para linfonodos mesentéri-cos, em alguns animais.…”
Section: Ensaios Clínicosunclassified